2016
DOI: 10.1136/thoraxjnl-2015-207949
|View full text |Cite
|
Sign up to set email alerts
|

Transplacental sildenafil rescues lung abnormalities in the rabbit model of diaphragmatic hernia

Abstract: In the rabbit model for DH, antenatal sildenafil rescues vascular branching and architecture, reduces pulmonary vascular resistances and also improves airway morphometry and respiratory mechanics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
79
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 57 publications
(95 citation statements)
references
References 39 publications
(38 reference statements)
12
79
1
3
Order By: Relevance
“…We focused primarily on the physiological effects of antenatal sildenafil treatment in DH lambs, so our study is limited by the absence of histological evidence to confirm the morphological and biochemical features underlying the observed physiology. However, the effects of sildenafil on pulmonary vascular development have been well described in other animal models of CDH and correlate well with our current findings. Interestingly, fetal plasma sildenafil concentrations in our lambs immediately prior to delivery (2–5 ng/mL) were similar to those obtained in rats by Mous et al ,.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We focused primarily on the physiological effects of antenatal sildenafil treatment in DH lambs, so our study is limited by the absence of histological evidence to confirm the morphological and biochemical features underlying the observed physiology. However, the effects of sildenafil on pulmonary vascular development have been well described in other animal models of CDH and correlate well with our current findings. Interestingly, fetal plasma sildenafil concentrations in our lambs immediately prior to delivery (2–5 ng/mL) were similar to those obtained in rats by Mous et al ,.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, antenatal treatment with the PDE‐5 inhibitor sildenafil has been shown to attenuate pulmonary vascular abnormalities in both a nitrofen‐induced CDH rodent model and a surgery‐induced CDH rabbit model, which is more clinically relevant in terms of lung development. In these animal studies, antenatal sildenafil treatment increased cGMP and vascular endothelial growth factor expression in lung tissue, increased distal pulmonary vessel density, decreased pulmonary vascular muscularization, reduced right ventricular wall thickness and increased distal airway complexity. However, it is unclear if these improvements in pulmonary vascular structure and biochemistry translate to improved pulmonary hemodynamics after birth.…”
Section: Introductionmentioning
confidence: 99%
“…The improved vascularisation was paralleled by reduced pulmonary artery pressure and by morphological changes in the lung parenchyma and functional improvement. In line with previous rodent studies, Russo et al 1 found that the decreased lung weight due to CDH is not rescued in sildenafil-treated fetuses with CDH, suggesting that the sildenafil-induced improvement of vascular and alveolar development contributes to the lung maturation more than the volume growth. These well-performed studies obtained in an animal model that closely resembles both the pharmacokinetics of human pregnancy and alveolar development in humans provide a next step towards a clinically useful therapy for CDH and its postnatal consequences.…”
supporting
confidence: 83%
“…Russo et al 1 demonstrate that maternally administered sildenafil reaches therapeutic levels in the rabbit fetus, without toxicity for mother or the fetus. CDH fetuses treated with sildenafil demonstrated increased pulmonary vascular branching compared with placebo-treated fetuses.…”
mentioning
confidence: 99%
“…We and others have performed some studies on the antenatal use of the phosphodiesterase-5 inhibitor sildenafil in different animal models of CDH, showing improvement in alveolarisation and pulmonary vascular development [57][58][59][60][61]. However, the pulmonary pathology in these treated animals did not show complete reversal to the normal lung histology.…”
Section: Treatment Of Pulmonary Vascular Defects In Cdhmentioning
confidence: 99%